The Effect of the Barman Model on Developing Academic Engagement among Students of the Art Education Department in the Course of Educational Theatre - Asst. Lect Weam Nadeem Jabir Al-Allaak (Journal of College of Education, 2026)
The current research aims to identify the effect of the Barman Model on developing academic engagement among students of the Art Education Department in the subject of Educational Theatre. To achieve this goal, the researcher constructed an Academic Engagement Scale consisting of (21) items. After verifying its validity and reliability, the scale was applied to a sample drawn from first-year students in the Department of Art Education / College of Basic Education / Al-Mustansiriyah University. The sample included (42) students in the experimental group and (40) students in the control group. The researcher adopted the experimental method and used the Statistical Package for the Social Sciences (SPSS) for data analysis.After implementing the instructional plans and research tools, the results indicated that the experimental group outperformed the control group. The findings suggest that teaching according to the Barman Model contributed to enhancing academic engagement among students of the Art Education Department through several key aspects, including students’ increased effort, interaction, and persistence in academic work; the strengthening of learners’ emotional states during learning activities; and the encouragement of students to be prepared for life and open to their surrounding environment.. Based on these results, the researcher recommends adopting the Barman Model within educational programs that aim to enhance academic engagement, as well as holding seminars and workshops for students to raise awareness of the importance of academic engagement. The researcher also suggests conducting further studies on the effect of the Barman Model in promoting academic ambition and exploring the relationship between academic engagement and mental wandering among students of Colleges of Basic Education.
Keywords: Barman Model, Academic Engagement, Educational Theatr